Spatio-temporal analysis of agricultural diversification in Bareilly district, Uttar Pradesh - Syed Rajab Ali; Mumtaj Ahmad (National Geographical Journal of India, 2025)
Agricultural diversification, the process of shifting from mono-crop to multi-crop systems, holds significant implications for sustainable development, food security, and economic resilience. This research paper shows spatio-temporal analysis of agricultural diversification patterns to understand their dynamics and associated factors. Utilising remote sensing data, Geographic Information Systems techniques, and statistical modelling, this study investigates the spatio-temporal changes of agricultural diversification across different regions. By integrating socio-economic and environmental factors, such as land use policies, climate variability, market demands, and socio-cultural influences, the researchers aim to identify key drivers of agricultural diversification trends. The analysis employs advanced spatial analytics to delineate hotspots of diversification, assess their resilience to environmental stressors, and evaluate their impact on local livelihoods and food systems. Furthermore, the study explores the role of technological innovations and agricultural practices in fostering diversification and enhancing agricultural productivity. The findings provide valuable perceptions for government, agricultural practitioners, and shareholders to formulate targeted interventions and strategies for promoting sustainable agricultural development and resilience in the face of global challenges.